KONSEP PERTUNJUKAN TEATER AKHUDIAT: PANGGUNG KOSONG KE TEATER JALANAN - Candra, Iga Ayu Intan (LP2M IAIN Ambon, 2020)
Abstract This study aims to examine Akhudiat as a theater figure in East Java in the form of thoughts about the concept of the Empty Stage Performance to the Street Theater. This research is a qualitative research with a narrative approach. Narrative stories in research tell individual experiences, collected through various forms of data, arranged chronologically, analyzed, contain turning points and take place in specific places and situations. Akhudiat has the idea of an Empty Stage to Street Theater, Empty Stage is a representation of the Akhudiat script and Street Theater is a theater designation that results from the directing of Akhudiat which is sourced from its manuscripts. Empty Stage is a concept that was carried by Akhudiat in writing the script. All Akhudiat manuscripts use the concept of Empty Stage which does not specify the form of setting so that the director can freely translate the manuscript. Ideas do not have to be bound, ideas are freed, the stage as a space of ideas that frees all supporting elements of the show to imagine and is called Street Theater. Akhudiat thought seen from the representation of the manuscript and his work is a figure with a tendency to the latest theater work. With an obsession with poetry performances that are whole, containing elements of humor, the inclusion of elements of traditional theater, with the theme of the background of the lower classes, are symbolic, is the theater director (the director acts as both a script writer). Keywords: Akhudiat, Street Theater, Empty Stage, Theater Abstrak Penelitian ini bertujuan mengkaji Akhudiat sebagai tokoh teater di Jawa Timur berupa pemikiran tentang konsep pertunjukan Panggung Kosong ke Teater Jalanan. Penelitian ini merupakan penelitian kualitatif dengan pendekatan naratif. Cerita naratif dalam penelitian menuturkan pengalaman individual, dikumpulkan melalui beragam bentuk data, disusun secara kronologis, dianalisis, mengandung titik balik dan berlangsung di tempat dan situasi yang spesifik. Akhudiat memiliki pemikiran Panggung Kosong ke Teater Jalanan, Panggung Kosong merupakan representasi naskah Akhudiat dan Teater Jalanan adalah sebutan teater yang dihasilkan dari penyutradaraan Akhudiat yang bersumber dari naskah-naskahnya. Panggung Kosong adalah konsep yang diusung Akhudiat dalam menulis naskahnya. Semua naskah Akhudiat menggunakan konsep Panggung Kosong yang tidak menspesifikasi bentuk setting sehingga sutradara dapat bebas dalam menterjemahkan naskah. Gagasan tidak harus terikat, gagasan yang dibebaskan, panggung sebagai ruang gagasan yang membebaskan seluruh elemen pendukung pertunjukan untuk berimajinasi dan disebutlah Teater Jalanan. Pemikiran Akhudiat dilihat dari representasi naskah dan karyanya merupakan tokoh dengan kecenderungan karya teater mutakhir. Dengan obsesi pada pertunjukan puisi yang utuh , mengandung unsur humor, masuknya unsur teater tradisional, bertemakan latar belakang kaum kelas bawah, bersifat simbolik, merupakan teater sutradara (sutradara berperan sebagai penulis naskah sekaligus). Kata Kunci : Akhudiat, Teater Jalanan, Panggung Kosong, Teater